Characteristics and outcomes of young adults with Philadelphia‐negative myeloproliferative neoplasms. (25th April 2019) - Barzilai, Merav; Kirgner, Ilya; Avivi, Irit; Ellis, Martin; Dally, Najib; Rozovski, Uri; Lavi, Noa
Abstract: Objective: Approximately 10% of Philadelphia (Ph)‐negative myeloproliferative neoplasms (NPM) are diagnosed at young adulthood. We aim to define the features of this group. Methods: A multicenter retrospective study, including patients 18‐45 years of age, diagnosed with Ph‐negative MPN between 1985 and 2017. Results: One hundred nine patients were included, 37 with polycythemia vera (34%), 54 with essential thrombocytosis (50%), 15 with primary myelofibrosis (PMF) (14%), and 3 with MPN unclassifiable (3%). Median age was 33 years and 62 (57%) were females. During a median follow‐up of 8 years, 39 patients (37%) had at least one thrombotic event. 30/39 of events were venous (77%), 23/30 of which were splanchnic (77%). In 14/39 (36%), thrombosis preceded MPN diagnosis. In a multivariable analysis, only splenomegaly predicted for thrombosis (HR 5.6, CI: 1.4‐22). The 10‐year risk for secondary myelofibrosis was similar for ET and PV (0.13 vs 0.19, P = 0.51). The 10‐year risk for leukemic transformation or mortality was significantly higher for PMF (0.3, P = 0.04). Conclusions: The risks of mortality and of progression to MF/leukemia in young adults are similar to older population. Thrombotic events are frequently a presenting sign with a high incidence of venous, in particular splanchnic, events.